DECODING EXCEPTIONAL FRONTLINE SERVICE PERFORMANCE: THE ROLES OF EMPLOYEE MOTIVATION AND NON-PHYSICAL WORK ENVIRONMENT AT BALI’S PREMIERJEWELLERY STORE - Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Yani, Ni Kadek Merta (Jurnal MBE Manajemen Bisnis, Equilibrium, 2025)
This study examines the influence of employee motivation and the non-physical work environment on frontline service performance at UC Silver Gold, a renowned jewellery store in Bali, highlighting their role in delivering superior customer experiences and maintaining competitive advantage. Using a census approach, all 60 employees were surveyed through structured questionnaires. The analyses included validity and reliability tests, classical assumption tests, multiple linear regression, determination analysis, and t-tests and F-tests to assess the significance of individual and combined variables, respectively. The findings reveal that employee motivation positively and significantly impacts frontline service performance; the non-physical work environment also has a positive and significant effect on frontline service performance; and both variables together create a robust influence on the quality of services delivered. These results underscore the need for organizations to prioritize communication, managerial support, and a supportive organizational climate to enhance service delivery and exceed customer expectations. This research contributes to the field of marketing by providing empirical evidence on the interplay between internal workplace dynamics and frontline service performance. By integrating employee motivation and environmental factors into service quality frameworks, the study highlights strategic pathways for improving customer satisfaction and strengthening competitive positioning in both local and global markets.